A point of clarification - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
In Agricultural extension - where next? (Spore 51) it was stated that 'The introduction of swamp rice in Sierra Leone using improved varieties had the potential to greatly increase yields. This implied that swamp rice in Sierra Leone is of recent...